Edukasi mengenai pentingnya PHBS tatanan rumah tangga dalam meningkatkan derajat kesehatan masyarakat di Desa Medana Kecamatan Tanjung Kabupaten Lombok Utara - Putri Nuryana; Windah Anugrah Subaidah; Eka Wahyuningsih (Universitas Mataram, 2022)
Clean and healthy living behavior (PHBS) in the household order is to empower household members to know, be willing and able to practice and play an active role in the health movement in the community. PHBS in household order has 10 indicators that must be implemented. Teluk Dalem Hamlet in Medana Village has not yet fully implemented PHBS so that a PHBS extension work program is still being planned. The purpose of the counseling is to increase awareness and empowerment of the community in PHBS in Teluk Dalem Hamlet, Medana Village, Tanjung District, North Lombok Regency. The method used is counseling and evaluation monitoring in Teluk Dalem Hamlet by providing materials, discussions, questions and answers and demonstrations. The results of filling out the PHBS questionnaire were births by health workers (100%); exclusive breastfeeding (80%); weigh the baby every month (70%); use of clean water (85%); wash hands with soap (60%); house free from mosquito larvae (40%); consumption of fruit and vegetables (70%); physical activity (50%); no smoking in the house (25%); and use of healthy latrines (75%). The conclusion in this community service can have an impact on increasing the health status of Teluk Dalem Hamlet, Medana Village, among others, increasing public knowledge about clean and healthy living behavior (PHBS), and being able to practice good handwashing behavior so as to avoid various diseases.